IMPLIKASI MAZHAB QIRA’AT AL-QUR’AN DALAM PENDIDIKAN ISLAM - Abdullah AS (SHAHIH (Jurnal Ilmu Kewahyuan), 2018)
“Qira'at al-Qur'an is a particular school in the pronunciation of the Qur'an adopted by a priest qira'at that is different from other schools based on the narrative which is connected to the Prophet Saw. and rated mutawatir. Such as qira'at al-sab 'and qira'at al-'asyarah. The occurrence of difference qiraat it is influenced by many factors.”